Custom Made Hand Painted Iris Ocular Prosthesis: A Case Report - Mohamed, Nusima; Azahar, Muhammad Amin (Indonesia Prosthodontic Association, 2021)
Trauma to eye, tumor, severe eye disease and infection can cause enucleation of the eye resulting to permanent defect of sight and aesthetic. Defects because of removing part of or the entire orbit will interfere to the patient’s psychology and confidence. Thus, by restoring the defect with custom made ocular prosthesis will restore aesthetics and improve their life in community. This is a case report of construction the natural look of a custom-made ocular prosthesis of a patient with missing her left eye due to trauma. The iris was made by hand painted method to improve the aesthetic outcome. The case describes the construction process including the method of fabrication, fitting and maintenance. It is aimed to highlight the importance of good clinical skill and management, advantages of custom-made prosthesis as compared to prefabricated ocular prosthesis and maintenance by good hygiene practice to promised good prognosis and aesthetic satisfaction.